KEAMANAN INFORMASI PERPUSTAKAAN PUBLIK: STUDI KASUS DAN PENDEKATAN CIA TRIAD Erlina Wardani - Wardani, Erlina (Jurnal Informasi, Perpustakaan, dan Kearsipan (JIPKA), 2025)
The advancement of information technology has transformed the way libraries provide and protect access to information. Information security has become a crucial aspect in the context of open access services. This study aims to analyze the management of information system security in libraries using the CIA Triad approach (Confidentiality, Integrity, Availability) as well as the security framework from Whitman and Mattord. The method employed is descriptive qualitative, utilizing literature studies from two case studies: the Central Java Provincial Library and the National Library of the Republic of Indonesia. The research findings indicate that both libraries implement security components in terms of physical, operational, and partially communication technology aspects. However, there is no explicit implementation regarding communication security and network security comprehensively. These findings highlight the importance of holistically strengthening information security systems to maintain the availability, integrity, and confidentiality of information within the scope of digital libraries Keywords: information security, information system, CIA Triad, library.